Thinking on PHP Dynamic Website Development Technology in the Internet Background - Wang, Kanghua (Journal of Artificial Intelligence and Information, 2025)
In the current societal context, the connection between peoples lives and the internet has become increasingly close. Internet technology has become an integral part of social production and development. The use of dynamic networks in the context of the internet has further expanded the applications of the internet. In the development of dynamic websites, PHP dynamic web development technology has become the primary approach due to its unique advantages. This paper starts by analyzing the characteristics of PHP technology and dynamic networks. It presents scenarios for development and applications utilizing PHP dynamic web technology. Furthermore, considering the current state of internet technology, the paper outlines the primary development directions for future PHP dynamic websites. The aim is to provide references for the implementation and research of related endeavors.